Shear strength of high performance concrete beams. - Kong, Paul Y.L. (Curtin University, 1996)
An analytical and experimental investigation on the shear strength of High Performance Concrete (HPC) beams with vertical shear reinforcement or stirrups was carried out. The analytical work involved developing a theory based on the truss analogy, capable of predicting the response and shear strength of such beams subjected to combined bending moment and shear force.The experimental work comprised forty-eight beam specimens in eight series of tests. Most of the beams were 250 mm wide, 350 mm deep and had a clear span of approximately 2 metres. The largest beam was 250 mm wide, 600 mm deep and had a clear span of 3.1 metres. Test parameters included the concrete cover to the shear reinforcement cage, shear reinforcement ratio, longitudinal tensile steel ratio, overall beam depth, shear span-to-depth ratio and concrete compressive strength. The loading configurations included using one, two or four symmetrically placed concentrated loads on simply supported spans.The theory predicted the shear strength of the beams in the present study well. When beams from previous investigations were included, the theory also gave good prediction of the shear strength. Apart from this, comparisons of shear strength were also made with the predictions by the shear design provisions contained in the Australian Standard AS 3600 (1994), American Concrete Institute Building Code ACI 318-95, Eurocode EC2 Part 1 and Canadian Standard CSA A23.3-94. The AS 3600 method was found to give the best correlation with the test results among all the code methods.